2019
DOI: 10.3390/ani9080573
|View full text |Cite
|
Sign up to set email alerts
|

Omega-3 and Omega-6 Fatty Acids in Poultry Nutrition: Effect on Production Performance and Health

Abstract: Omega-3 (ω-3) and omega-6 (ω-6) fatty acids are important components of cell membranes. They are essential for health and normal physiological functioning of humans. Not all fatty acids can be produced endogenously owing to the absence of certain desaturases; however, they are required in a ratio that is not naturally achieved by the standard diet of industrialized nations. Poultry products have become the primary source of long-chain polyunsaturated fatty acids (LC-PUFA), with one of the most effective soluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
139
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 172 publications
(148 citation statements)
references
References 138 publications
(169 reference statements)
6
139
1
2
Order By: Relevance
“…Furthermore, dietary OCM and/or BL supplementation in the present investigation elevated the level of total protein and ND titer, which can be attributed to the improved immunity of broilers. Olive oil is a potent immunomodulator that can improve immunity and generate more pathogen resistance [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, dietary OCM and/or BL supplementation in the present investigation elevated the level of total protein and ND titer, which can be attributed to the improved immunity of broilers. Olive oil is a potent immunomodulator that can improve immunity and generate more pathogen resistance [5].…”
Section: Discussionmentioning
confidence: 99%
“…Any reduction in feed costs, which still preserves the health status of broilers, is bound to have a direct positive effect on the profitability of poultry production. A considerable effort has been applied to find alternative and sustainable protein sources to be included in broilers diets [5]. In this context, among the available plant protein alternatives, olive cake meal which has high nutritional value (lipids, 13-15%, and proteins, 9-10%), with a high level of non-starch polysaccharides (NSP) (xyloglucan and xylan-xyloglucan complexes) [3,[6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Good nutrition must be provided to maintain health (Abdelnour, Abd El-Hack, Alagawany, Farag, & Elnesr, 2019;Alagawany et al, 2019;Elnesr, Ropy, & Abdel-Razik, 2019). Prebiotic and probiotics were used to feed medication to improve feed intake and digestion (Abd El-Hack, Mahgoub, Alagawany, & Ashour, 2017;Alagawany et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…This is due to a higher content of phenolic substance and different minerals, especially selenium, in mushrooms. Dietary supplementing selenium could enhance the body weight gain and antioxidant enzyme activities in chickens [69]. The author finally concluded that the residue of Pleurotus eryngii mushroom could improve the antioxidant status in layer chickens.…”
Section: Application Of Medicinal Mushrooms On Health Status In Layermentioning
confidence: 96%